2010
DOI: 10.2527/jas.2010-3083
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and increased nutrient intake before and during gestation in the ewe results in altered growth, adiposity, and glucose tolerance in adult offspring1

Abstract: We evaluated the effects of preconception and gestational obesity in the ewe on offspring growth, metabolism, and glucose homeostasis. From 60 d before conception through parturition, multiparous ewes were fed 100% (control; n = 8) or 150% (obese, OB; n = 10) of NRC (1985) recommendations. Ewes on the OB diet increased BW by 30% from diet initiation to mating (P = 0.03) and by 52% by d 135 of gestation (P = 0.04), whereas control ewes increased BW by 7% (P = 0.65) from diet initiation to d 135 of gestation. La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
3
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(141 citation statements)
references
References 37 publications
8
127
3
3
Order By: Relevance
“…Interestingly, in the current study Fat gilts had a 25% increase in milk fat at day 21 of lactation than Thin gilts (Amdi et al, 2013), which may have contributed to the increased piglet weight gain. In agreement with our results, Long et al (2010), found that offspring born from obese ewes, consumed 10% more feed than offspring born from control ewes when the offspring where ad libitum fed over a 12-week period from 19.5 ± 0.5 months of age. Recent studies have addressed the issue that perhaps maternal body composition by itself is a programming agent for growth of the offspring.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in the current study Fat gilts had a 25% increase in milk fat at day 21 of lactation than Thin gilts (Amdi et al, 2013), which may have contributed to the increased piglet weight gain. In agreement with our results, Long et al (2010), found that offspring born from obese ewes, consumed 10% more feed than offspring born from control ewes when the offspring where ad libitum fed over a 12-week period from 19.5 ± 0.5 months of age. Recent studies have addressed the issue that perhaps maternal body composition by itself is a programming agent for growth of the offspring.…”
Section: Discussionsupporting
confidence: 92%
“…In longer-term studies, following early gestation maternal food restriction, Sebert et al (2009) reported no effect on appetite in obese 1-year-old offspring, but George et al (2012) reported increased appetite drive in obese female 6-year-old offspring. Conversely, Long et al (2010a) reported increased appetite at 19 months of age in the offspring of overnourished obese mothers.…”
Section: Epigenetic Programming Of Appetite Regulationmentioning
confidence: 99%
“…Hence, undernutrition during pregnancy in pigs is associated with increased adiposity of progeny in later life, but the sensitive time for the effect is still unclear. There is also one cattle study (Long et al 2010a) suggesting that overnutrition throughout gestation results in increased adiposity in older offspring (at 22 vs 19 months). Cattle studies by Micke et al (2010aMicke et al ( , 2011aMicke et al ( , 2011b show that the maternal diet during the first and second trimesters alters growth and carcass development, including fat deposition, from weaning through to slaughter at 22 months of age in a sex-specific manner.…”
Section: Body Fat or Adipositymentioning
confidence: 99%
“…Because of the nondiscreet timing of the maternal over-nutrition reported by Long et al (2010), it is not known whether early or late gestational nutrition excess contributed to the increased appetite. Muhlhausler et al (2006) reported that in sheep, over-nutrition during late gestation resulted in increased milk intake and subcutaneous fat accumulation accompanied by an unpredicted increased expression of POMC, but not CART mRNA at 30 days postnatally.…”
Section: Discussionmentioning
confidence: 99%